A new species of Cirratulus (Annelida: Polychaeta) described from a shallow-water whale bone in Antarctica - Taboada, Sergi; Doner, Stacy; Blake, James A.; Avila, Conxita (Zootaxa, 2012)
A new species of Cirratulus Lamarck, 1818 is described from the shallow Antarctic waters of Deception Island (SouthShetland Islands). Cirratulus balaenophilus sp. nov. is the first cirratulid to be described from a fresh whale bone that wasexperimentally deployed for one year on the Antarctic sea floor. The species is characterized by the lack of spines andeyes, the number of dorsal tentacles arranged in an arc, and its light yellow-orange color in life. The cytochrome c oxidasesubunit I (COI) sequence is presented, as well as some remarks about its feeding preferences and ecology. A comparison with congeneric species occurring in Antarctica and adjacent waters is also provided.